2022
DOI: 10.1097/mco.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related malnutrition in chronic kidney disease

Abstract: Purpose of reviewDisease-related malnutrition has complex and multifactorial pathophysiology. It is common in patients with chronic kidney disease (CKD) and has a devastating impact on morbidity and mortality. Given the rising numbers of patients diagnosed with CKD, disease-related malnutrition is an escalating clinical challenge. This review summarises current knowledge in relation to the development, screening and treatments for disease-related malnutrition in CKD Recent findingsNew research has identified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our analysis indicated similar results with consistent effects on muscle strength, and some on performance, but also with inconsistent effects on muscle mass. Of the high protein ONS nutritional studies [ 4 ], we found they also had a beneficial effect but no consistency with improving muscle mass, and this might relate to dose used. We noted that key factors relating to exercise participation and adherence, longer term intervention durations, progressive loading and higher intensities were potentially favourable in promoting significant gains.…”
Section: Exercise Strategies For Renal Cachexiamentioning
confidence: 79%
See 1 more Smart Citation
“…Our analysis indicated similar results with consistent effects on muscle strength, and some on performance, but also with inconsistent effects on muscle mass. Of the high protein ONS nutritional studies [ 4 ], we found they also had a beneficial effect but no consistency with improving muscle mass, and this might relate to dose used. We noted that key factors relating to exercise participation and adherence, longer term intervention durations, progressive loading and higher intensities were potentially favourable in promoting significant gains.…”
Section: Exercise Strategies For Renal Cachexiamentioning
confidence: 79%
“…A number of overlapping nutrition-related syndromes are prevalent in chronic kidney disease (CKD) patients, such as disease-related malnutrition, cachexia, protein-energy wasting (PEW), sarcopenia and frailty [2–5] Cachexia has been defined as “a complex metabolic syndrome associated with underlying illness and characterized by loss of muscle with or without loss of fat mass”, and linked to reduced quality of life (QoL), increased morbidity, disability and mortality [6]. Cachexia is closely related to PEW and may be considered as a more progressive and advanced degree of wasting [3].…”
Section: Introductionmentioning
confidence: 99%
“…ii. Dietary counselling—Chronic disease-related malnutrition in ESKD is a complex issue given that disease specific factors such as inflammation must also be taken into consideration [ 19 , 20 ]. Koppe, Fouque & Kalantar-Zadeh [ 6 ] confirm that PEW is among the strongest predictors of mortality in patients with ESKD (hazard ratio of 3.03; confidence interval of 1.69–5.26 in 1068 haemodialysis patients).…”
Section: Steps To Develop the Toc Mapmentioning
confidence: 99%
“…Evidence suggests that providing nutrition counselling could be linked to improvements in the patients’ malnutrition inflammation scores and nutritional knowledge and status [ 61 , 62 ]. Disease-specific nutritional guidance and supplementation to provide adequate protein, energy and preserve lean muscle mass is therefore essential to the health of haemodialysis patients [ 19 , 94 , 95 , 96 , 97 , 98 , 99 ]. Evidence suggests that nutritional therapy and nutritional supplementation to renal patients during haemodialysis is an ideal opportunity to manage the PEW pathology actively and help to manage one of the most critical risks for mortality in haemodialysis patients [ 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Steps To Develop the Toc Mapmentioning
confidence: 99%
See 1 more Smart Citation